1997
DOI: 10.1021/bi9714464
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Glutathionyl-Enzyme Intermediate in the Amidase Activity of the Bifunctional Glutathionylspermidine Synthetase/Amidase from Escherichia coli

Abstract: Glutathionylspermidine (Gsp) is a metabolite common to Escherichia coli and protozoal parasites of the Trypanosoma family. Though its role in E. coli is unknown, Gsp is known to be an intermediate in the biosynthesis of N1,N8-bis(glutathionyl)spermidine (trypanothione), a metabolite unique to trypanosomatids that may allow the parasites to overcome oxidative stresses induced by host defense mechanisms. The bifunctional Gsp-synthetase/amidase from E. coli catalyzes both amide bond formation and breakdown betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
(40 reference statements)
3
28
0
Order By: Relevance
“…TcTryS also has an opposing amidase activity, which is about 1% of the synthetase activity when assayed at pH 8.0 near the optima for the forward and reverse reactions. This is consistent with our finding that TcTryS has an N-terminal domain containing a conserved Cys (at position 51) previously shown to be essential for amidase activity in both E. coli (35) and C. fasciculata (27). However, the amidase activity of TcTryS with glutathionylspermidine is two orders of magnitude lower than that observed for GspS from C. fasciculata, when assayed under identical conditions (Table II).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…TcTryS also has an opposing amidase activity, which is about 1% of the synthetase activity when assayed at pH 8.0 near the optima for the forward and reverse reactions. This is consistent with our finding that TcTryS has an N-terminal domain containing a conserved Cys (at position 51) previously shown to be essential for amidase activity in both E. coli (35) and C. fasciculata (27). However, the amidase activity of TcTryS with glutathionylspermidine is two orders of magnitude lower than that observed for GspS from C. fasciculata, when assayed under identical conditions (Table II).…”
Section: Discussionsupporting
confidence: 92%
“…Significant homology was found between TcTryS and EcGspS in the N-terminal region, which is responsible for the glutathionylspermidine amidase activity of the E. coli protein (28,34). Moreover, a cysteine residue, corresponding to Cys-59 of EcGspS and Cys-79 Cf GspS that have been shown by site-directed mutagenesis to be essential for amidase activity (27,35), is present in TcTryS, suggesting that this enzyme may also possess amidase activity (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reagents and Chemicals-The chromogenic tripeptide ␥-Glu-Ala-Gly-p-nitroanilide (␥-EAG-pNA), which was the amidase substrate, was synthesized as reported (10). The thiol-labeling reagent, monobromobimane (mBBr) and (GspS) 2 were purchased from Bachem and Invitrogen, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The function of this compound in E. coli is not known, although it has been suggested that it is involved in regulating the levels of the precursors (spermidine and glutathione). More recently, Bollinger et al (23)(24)(25) reported the cloning and characterization of a bifunctional E. coli glutathionylspermidine synthetase/amidase enzyme responsible for both the biosynthesis and degradation of glutathionylspermidine in E. coli.…”
mentioning
confidence: 99%